Investigating the Performance of Hydroponic Nutrient Solutions as Potential Draw Solutions for Fertilizer Drawn Forward Osmosis - Abu Qersh, Mohamed Bassiouny (AUC Knowledge Fountain, 2021)
This research project aims at investigating the performance of hydroponic nutrient solutions as draw solutions for desalination using the fertilizer drawn forward osmosis (FDFO) process. Six different lettuce and leafy greens hydroponic nutrient stock solutions were prepared according to the literature and used in this study and tested on a bench-scale forward osmosis unit as draw solutions for the process. The feed solutions for the process was de-ionized water mixed with Sodium Chloride in different concentrations to represent different salinities of brackish groundwater. The draw efficiency of each solution was measured based on water flux, reverse solute flux, water recovery, and salt rejection. This research project aims at reaching an efficient nutrient solution that would be economically feasible to be used in hydroponic agriculture of leafy greens, in non-arable areas which have access to brackish groundwater or seawater. By achieving this goal and developing a model for implementation, the burden that is currently being exerted on freshwater resources by inefficient agriculture in Egypt will hopefully be diminished, which would provide more drinking water. It was concluded that of the six tested nutrient solutions, the “Resh Florida, California (RF)” solution is the recommended solution to be used as draw solution for fertilizer drawn forward osmosis, due to its high performance in terms of water recovery (35.1 ml) & flux (11 l/m2/h), salt rejection (92%) & specific reverse solute flux (SRSF) (highest recorded SRSF for a specific ion (SO42-) was 7.3 g/l), as well as its low cost, relative to the other highly performing draw solution “Chekli (CHE)” ($1.07/l vs. $3.73/l). Future research endeavors could be directed at experimenting with other hydroponic nutrient solutions, experimenting with different types of membranes, testing the same solutions from this research on the pilot-scale, performing a life cycle analysis of the membrane after operation, and using the resultant draw solution from this process to grow crop hydroponically.